(untitled) - Hale, Judith A. (San Francisco, 2006)
In this book, human resource management and training expert Judy Hale demystifies training outsourcing and details how companies can successfully outsource their training and development needs—from the entire learning function to selected services and programs. It also covers the labyrinth of contractual, interpersonal, and legal dimensions inherent in any decision to partner with another service provider.
Keywords: Contracting out,Employees; Training of